2016
DOI: 10.1007/s00540-016-2197-y
|View full text |Cite
|
Sign up to set email alerts
|

Hematological predictors and clinical outcomes in cardiac surgery

Abstract: The triple combination of parameters obtained as part of the hemogram, NLR-RDW-MPV, indicated a much more predictive power than two parameters coupled. This combination of three parameters, NLR-RDW-MPV, is to be considered as a sensitive, high-quality, low-cost outcome prediction marker for cardiac surgery patients that is less time consuming and easy to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…[152122] It is considered as a sensitive and low-cost prognostication marker, which may combine with other hematological parameters (such as mean platelet volume or neutrophil-to-lymphocyte ratio) to provide better outcome predictive value. [23] However, the use of RDW among noncardiac surgical condition is less common. [1824] This study evaluated the value of preoperative RDW for prediction of 30-day mortality in patients who received major- or ultra-major noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[152122] It is considered as a sensitive and low-cost prognostication marker, which may combine with other hematological parameters (such as mean platelet volume or neutrophil-to-lymphocyte ratio) to provide better outcome predictive value. [23] However, the use of RDW among noncardiac surgical condition is less common. [1824] This study evaluated the value of preoperative RDW for prediction of 30-day mortality in patients who received major- or ultra-major noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a combination of RDW with mean platelet volume and neutrophil-to-lymphocyte ratio might offer better adverse events (defined as myocardial infarction, cardiac reoperation, prolonged mechanical ventilation, prolonged hospital stay, rehospitalization, and mortality) predictions among patients who received cardiac surgery. [23] Mizuno et al . also illustrated the potential benefit of RDW combined with Mehran Risk Score for the prediction of contrast-induced acute kidney injury in patients with ST-elevated myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, patients with high RDW are 1.8 times more likely to develop adverse events after cardiac surgery (OR 0.55, 95% CI [0.365-0.852], p=0.007). 7 In another cohort (n=16,631), after non-cardiac surgery, the area under the curve was 0.761 (95% CI [0.736-0.787]) using a cut-off value of RDW 15.7% with a specificity of 89.3% and a negative predictive value of 99% for predicting 30-day mortality. 8 In contrast, in another cohort (n=217,567) RDW >14% was associated with metabolic syndrome (OR 1.14; 95% CI [1.07-1.21]; p<0.0001).…”
mentioning
confidence: 97%
“…10 Moreover, RDW >14.9% is associated with increased major bleeding risk (HR 2.41, 95% [CI 1.15-5.02], p=0.02) in non-STsegment elevation MI (NSTEMI). The addition of RDW to the Can Rapid risk stratification of Unstable angina patients Suppress ADverse outcomes with Early implementation of the ACC/AHA guidelines (CRUSADE) bleeding score had a significant integrated reclassification improvement of 10% (95% CI [6][7][8][9][10][11][12][13][14][15][16][17][18][19]; p=0.02). 11 Similarly, another study showed that RDW was a predictor of major bleeding and that with the addition of RDW as a continuous variable to the National Cardiovascular Data Registry risk model, net reclassification improvement increased by 17.3% (95% CI [6.7-28]; p=0.02).…”
mentioning
confidence: 99%
“…The mortality rate increases when the need for a transfusion increases [17]. In a number of similar studies in recent years, preoperative low hematocrit levels in cardiac surgery have been shown to trigger postoperative complications [18,19]. Ranucci et al examined 3,003 patients who underwent isolated CABG surgery.…”
Section: Discussionmentioning
confidence: 99%